Penyaluran Zakat Kepada Ulama di Kecamatan Astambul Kabupaten Banjar - Nashih, Muhammad (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this research is to find out how the distribution of zakat to the ulemas on the welfare of the community in Astambul District, Banjar Regency. The majority of people in Astambul District, Banjar Regency, distribute zakat to scholars compared to other mustahik. This of course will have an impact on the welfare of the clergy and the poor and can ultimately result in inequality of welfare. This research is field research conducted in Astambul District, Banjar Regency. By observing the description of the activities, the author uses a qualitative descriptive method to try to gather information and solve problems. The description is then analyzed to find out how zakat is distributed to the clerics in Astambul District, Banjar Regency. Analysis can also be used to find out how the impact of the distribution of zakat to scholars has on mustahik who live in the vicinity. This study produced many first findings: the distribution of zakat to scholars is carried out personally. Second: the community distributes zakat to scholars in the hope of getting the blessings of a scholar and repaying teachers who have taught them knowledge. Third: the majority of scholars who receive zakat from muzakki do not keep it for themselves, but distribute it back to those who need it most in the form of alms so that this distribution does not affect welfare inequality. Keywords: Distribution, Zakat, Ulema